(untitled) (RUNA, archivo para las ciencias del hombre, 2016)
Evaluadores Nacionales Magdalena Arnao, Universidad Nacional de Córdoba María Gabriela Chaparro, Universidad Nacional del Centro de la Pcia. de Buenos Aires Emilio Crenzel, Universidad de Buenos Aires Daniel Feierstein, Universidad Nacional de Tres de Febrero Ana María Gorosito Kramer, Universidad Nacional de Misiones Anne Gustavsson, Universidad Nacional de San Martín Paula Silvana Novellino, Museo de Ciencias Naturales y Antropológicas Juan Cornelio Moyano Natalia Ojeda, Universidad Nacional del Centro de la Pcia. de Buenos Aires Francisco Pazzarelli, Universidad Nacional de Córdoba Jaime Peire, Universidad Nacional de Tres de Febrero Ana Ramos, Universidad Nacional de Río Negro Agustina Rodríguez Romero, Universidad Nacional de Tres de Febrero Carlos Salamanca, Flacso – Argentina. Jorge Suby, Universidad Nacional del Centro de la Pcia. de Buenos Aires Evaluadores Extranjeros Karina Biondi, Universidade Estadual de Campinas, Brasil Vincent Hirtzel, Centre National de la Recherche Scientifique – CNRS, Francia María Isabel Jociles Rubio, Universidad Compultense de Madrid, España Liuba Kogan, Universidad del Pacífico, Perú Diana Marre, Universidad Autónoma de Barcelona, España Mario Ruffer, Universidad Autónoma Metropolitana, México